Comparison of telomere length and insulin-like growth factor-binding protein 7 promoter methylation between breast cancer tissues and adjacent normal tissues in Turkish women - GÜLLÜ AMURAN, GÖKÇE; KAYA, HANDAN; GÜLLÜOĞLU, MAHMUT BAHADIR; AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (WILEY, 2017)
BackgroundBoth insulin-like growth factor-binding protein 7 (IGFBP7) and telomere length (TL) are associated with proliferation and senescence of human breast cancer. This study assessed the clinical significance of both TL and IGFBP7 methylation status in breast cancer tissues compared with adjacent normal tissues. We also investigated whether IGFBP7 methylation status could be affecting TL. MethodsTelomere length was measured by quantitative PCR to compare tumors with their adjacent normal tissues. The IGFBP7 promoter methylation status was evaluated by methylation-specific PCR and its expression levels were determined by western blotting. ResultsTelomeres were shorter in tumor tissues compared to controls (P<.0001). The mean TL was higher in breast cancer with invasive ductal carcinoma (IDC; n=72; P=.014) compared with other histological type (n=29), and TL in IDC with HER2 negative (n=53; P=.017) was higher than TL in IDC with HER2 positive (n=19). However, telomeres were shortened in advanced stages and growing tumors. IGFBP7 methylation was observed in 90% of tumor tissues and 59% of controls (P=.0002). Its frequency was significantly higher in IDC compared with invasive mixed carcinoma (IMC; P=.002) and it was not correlated either with protein expression or the other clinicopathological parameters. ConclusionThese results suggest that IGFBP7 promoter methylation and shorter TL in tumor compared with adjacent tissues may be predictive biomarkers for breast cancer. Telomere maintenance may be indicative of IDC and IDC with HER2 (-) of breast cancer. Further studies with larger number of cases are necessary to verify this association.
Keywords: breast cancer; insulin-like growth factor-binding protein 7; methylation; telomere; telomere length; TIME QUANTITATIVE PCR; MALIGNANT-TRANSFORMATION; CELLULAR SENESCENCE; COLORECTAL-CANCER; GENE-EXPRESSION; DOWN-REGULATION; CELLS; IGFBP7; ASSOCIATION; CARCINOMA